IMPLEMENTASI KURIKULUM MERDEKA (STUDI KASUS DI SMP PONPES MANBAUL HIKMAH KALIWUNGU) - suciptono (Istifkar: Media Transformasi Pendidikan, 2022)
The 2013 curriculum is the curriculum that has been implemented so far as the national curriculum since the 2013/2014 school year. The emergency curriculum is a learning loss recovery curriculum that occurs in special conditions and has the principle of diversification which refers to the 2013 curriculum with core competencies and basic competencies but is simplified and implemented during the Covid-19 learning period. Meanwhile, the independent curriculum is a curriculum that was formerly known as a prototype curriculum which was later developed as a more flexible curriculum framework, while also focusing on essential material and character development and student competencies. The program revealed by the Minister of Education and Culture Nadiem Anwar Makarim has attracted a lot of attention from education observers. Manbaul Hikmah Kaliwungu Middle School is one of the schools that pioneered implementing the independent curriculum. This school has implemented an independent curriculum for less than one year. The application of the Independent Curriculum also includes learning Islamic religious education. This school has operated quite well in implementing the independent curriculum in learning, even though there are some obstacles that occur in it. However, the implementation of the independent curriculum in Islamic religious education subjects can still run well. In the implementation stage of the independent curriculum, the principal thought of the SMP Manbaul Hikmah Kaliwungu principal is the integration of the typical Manbaul Hikmah curriculum, namely the Kaffah curriculum. So that as a driving school that previously implemented a prototype curriculum, it changed to implementing an independent curriculum. Even so, this change did not dampen the spirit of the school principal to be optimistic that SMP Manbaul Hikmah Kaliwungu would be able to implement it.